RENEB interlaboratory comparison for biological dosimetry based on dicentric chromosome analysis and cobalt-60 exposures higher than 2.5 Gy - Bucher, Martin; Endesfelder, David; Pojtinger, Stefan; Baeyens, Ans; Barquinero, Joan-Francesc; Beinke, Christina; Bobyk, Laure; Gregoire, Eric; Hristova, Rositsa; Martinez, Juan S; Meher, Prabodha Kumar; Milanova, Marcela; et al. (Scientific reports, 2025)
In previous RENEB interlaboratory comparisons based on the manual scoring of dicentric chromosomes, a tendency for systematic overestimation for doses > 2.5 Gy was found. However, these exercises included only very few doses in the high dose range, and they were heterogeneous in terms of radiation quality and evaluation mode, and comparable only to a limited extent. Here, this presumed deviation was explored by investigating three doses > 2.5 Gy. Blood samples were irradiated (2.56, 3.41 and 4.54 Gy) using a 60Co source and sent to 14 member laboratories of the RENEB network, which performed the dicentric chromosome assay (manual and/or semi-automatic scoring) and reported dose estimates. Most participants provided estimates that agreed very well with the physical reference doses and all provided dose estimates were in the correct clinical category (> 2 Gy). The previously observed tendency for a systematic bias across all laboratories was not confirmed. However, tendencies for systematic underestimation were detected for dose estimations for reference doses given in terms of absorbed dose to blood and for some participants, a laboratory-specific trend of systematic under- or overestimation was observed. The importance of regularly performed quality checks for a broad dose range became obvious to avoid misinterpretation of results.
Keywords: laboratoře; Radiometry; Laboratories; lidé; Radiation Dosage; mužské pohlaví; Cobalt Radioisotopes; Dose-Response Relationship, Radiation; Male; chromozomální aberace; dávka záření; vztah dávky záření a odpovědi; Chromosome Aberrations; radioizotopy kobaltu; radiometrie; Humans